(untitled) (Tạp chí Y học Cộng đồng, 2026)
Background: Post-vaccination reactions, caused by the body’s immune response to vaccines, range from mild to severe and may pose risks to children. This study sought to identify key predictive factors for severe post-vaccination reactions among children under five years old treated at the Vietnam National Pediatric Hospital. Methodology: A cross-sectional descriptive study was conducted on 103 pediatric patients who experienced adverse reactions following vaccination between January 2019 and December 2021. Results: Among the pediatric patients, 43.7% were female, and 42 children (40.8%) experienced severe reactions. A significant correlation was found between prior abnormal vaccine reactions and severe outcomes (OR = 2.525, 95% CI: 1.019–6.261; p = 0.042). Additionally, delayed access to the first healthcare facility (over one hour) significantly increased the risk of severe reactions (OR = 2.821, 95% CI: 1.074–7.405; p = 0.031). Conclusion: Identifying these prognostic factors contributes to enhancing expanded immunization programs for children and preventing severe post-vaccination reactions, ultimately improving pediatric care and safety.